The Investigation of the Awareness of Implementing Blockchain Technology in Audit Trails among the Auditors - Jayathilake, N. W. Deepashika; Seneviratne, S M Chaturika (Journal of Accounting Research, Organization and Economics, 2022)
Objective - The purpose of this study is to investigate the awareness of implementing blockchain technology in audit trails among Sri Lankan auditors.Design/ methodology - Exploratory research is conducted to investigate the awareness among the auditors regarding the implementation of blockchain technology in the audit trails. A qualitative research approach is applied to collect data through semi-structured interviews with auditors employed in a leading audit firm in Sri Lanka.Results There is a relatively lack of awareness about blockchain technology among auditors in general, which could be a roadblock to blockchain implementation in audit trials in Sri Lanka. Since blockchain has demonstrated potential as a technology that can transform auditing processes, there is possibility to build an audit trail, although more study is needed in this sector to be successful. Regardless matter where blockchain and audit trails go in the future, the audit profession will undoubtedly be impacted; however, it is yet too early to predict how.Research limitations/ implications - This analysis has taken a restricted perspective by relying just on auditors at one audit firm in Sri Lanka. If the perspectives and information of various auditing firms had been included, the study would have had a lot more to explore and analyze.Novelty/ originality - This study contributes to the literature on blockchain technology in audit trials by documenting the existing knowledge of auditors. This will provide an in-depth comprehension of using blockchain technology in audit trials to clients, professionals, and overall society.